Environmental Education for Sustainable Development: A Bibliometric Review of Curriculum Design and Pedagogical Approaches - Lasino; Arief Yanto Rukmana; Sabil Mokodenseho; Adit Mohammad Aziz (The Eastasouth Journal of Learning and Educations, 2023)
Environmental education plays a pivotal role in fostering a sustainable future by equipping individuals with the knowledge, skills, and attitudes needed to address complex environmental challenges. This research presents a comprehensive bibliometric review of the literature on environmental education for sustainable development, with a specific focus on curriculum design and pedagogical approaches. The analysis encompasses a wide range of scholarly articles published between 1961 and 2023, providing valuable insights into the current state of research in this field. Furthermore, the research employs VOSviewer, a bibliometric software, to analyze co-citation and bibliographic coupling networks, identifying influential authors, prominent journals, and emerging trends within the field. The most frequent and fewer occurring keywords are compared to highlight central concepts and potential areas for further research. The results of this study contribute to a comprehensive understanding of the diverse themes, effective practices, and influential contributors in environmental education for sustainable development. By identifying key areas of focus and research gaps, educators, policymakers, and researchers can design targeted interventions and initiatives that promote environmental literacy, responsible behavior, and sustainable practices among learners. Ultimately, this research seeks to advance the field of environmental education and empower individuals to become active stewards of the environment, shaping a more sustainable and resilient future for all.